Control Of Transmission Power And Carrier Sense Threshold To Enhance Throughput And Fairness For Dense WLANs - Roslan, Irda; Kawasaki, Takahiro; Nishiue, Toshiki; Takaki, Yumi; Ohta, Chikara; Tamaki, Hisashi (IEEE Computer Society, 2016)
Carrier Sense Multiple Access with Collision Avoidance (CSMA/CA) adopted in IEEE 802.11 WLAN suffers from serious problems of hidden terminal and exposed terminal. This will get worse if the environment becomes highly dense. The rise of channel interference among stations (STA) and the deterioration of the total network throughput as the result of these terminal problems need to be mitigated. A possible solution is to enable STAs to control transmission power and carrier sense threshold based on the information retrieved from the access point (AP). However, broadcasting message frames from AP to all STAs for identification purpose will cause much overhead. The proposed control scheme applies Bloom filter to distinguish associated STAs within the same basic service set (BSS) from the others while minimizing the overhead. The aim of this proposed scheme is to enhance the total throughput of the network and improve fairness of each STA in dense WLAN.